The Impact of Hedging in Reducing Loss of Exchange Rate - Ending Ridwan (Universitas Trisakti, 2006)
Today, not a single country could act as a sole provider towards its own needs for food, energy, finance, communication and information. It requires other countries which then creates interdependent relationships. What started as merely barter then gradually increased into a form of currency which function as one of a nation's identities. However not every country can use its own currency when engaging in export import activities, only developed countries are capable of doing so, whereas developing countries are required to have huge amount of reserve and capital in order to minimize the risk. Financial risk will always exists but there three ways to control them. through insurances, asset or liability management, and hedging. This article aimed to know how far he depreciation of Rupiah could result in exchange loss. Second, is to identify the hedging impact in order to avoid or minimize exchange loss. The author choose 15 companies listed in Jakarta Stock Exchange which possess an asset over 5 trillion Rupiah. The Solving method narrowed them down into 9 companies. The data used in this article is secondary, originated from end of year financial report starting from 1997 until 2001. The methodology is descriptive and correlational research.